Waterborne epoxy sizing agent with hyperbranched structure to improve the interface performance of carbon fiber. Issue 4 (14th January 2021) - Chen, Yifan; Ding, Lei; Chai, Mingzhuo; Liu, Li; Huang, Yudong
Abstract: The epoxy resin was modified by hyperbranched structure of hydroxyl terminated to obtain waterborne epoxy resin for using as the carbon fiber (CF) sizing agent. By mixing method of waterborne epoxy resin and water, the waterborne epoxy sizing agent can be fabricated directly. In the sizing process, free of volatile organic solvents ensure the safety of operators and environment. Moreover, the introduction of tertiary amine group in hyperbranched structure will promote the reaction between epoxy and hydroxyl groups, and thus enhance the bonding strength between CF and epoxy resin. Results showed that the introduction of sizing agent does not sacrifice the CF single fiber tensile strength. The structure of epoxy resin retained in sizing agent is beneficial to the good wettability between CF and epoxy resin according to surface energy results. Interfacial shear strength value increases from 51.75 to 72.34 MPa, and interlaminar shear strength value increases from 80.32 to 90.34 MPa. These mechanical properties show that hyperbranched epoxy resin sizing agent with a large amount of hydroxyl groups can effectively improving the interface adhesion between CF and epoxy resin, showing a broad application prospect in composite materials field. Abstract : Waterborne epoxy sizing agent with hyperbranched structure to improve the interface performance of carbon fiber